Revisiting the Finality of Hadith Science: Formalization, Reformulation, and Western Scholars' Falsification - Muhammad Akmaluddin; Nur I’anah; Ashfa Nafilatir Rohmaniyah (Jurnal Living Hadis, 2026)
Classical hadith science has undergone relatively little development among Muslim Scholars, having come to be regarded as fully established and final (naḍīja wa iḥtaraqa). This stagnation was presented by Ibn Najīm and exists in the hadith science literature of the period. By contrast, Western scholarship has advanced considerably in methodology, theory, application, and historical analysis. This study addresses two questions. First, it maps classical and medieval hadith science through its phases of formalization and reformulation, before the emergence of Orientalism. Second, it examines how Western scholars’ falsification of hadith studies—both revisionist and traditionalist—might revive the field, including through critical engagement with formalization and continued reformulation via re-examination of existing theories. Using a historiographical approach to hadith literature from the 4th/10th to 14th/mid-20th–15th/21st centuries, and drawing on al-Jābirī’s theory of waṣl (continuity) and faṣl (rupture) alongside Popper’s falsification, findings show that hadith science is ijtihādī, developing, stagnating, and redeveloping. Formalization around al-Bukhārī’s standard led to misjudgments of traditions predating him or originating outside the Mashriq; Reformulations offered a little clear line of demarcation between multiple standards that are not standardized; and Western falsificationist critique has made hadith science more open, accommodating, and rigorous than formalized standards alone.